Obtenção e caracterização de monólitos nanoestruturados de BiFeO3- PbTiO3 - Protzek, Otávio Augusto (2015)
In this work we studied processes to obtain nanostructured ceramic samples (0.6) BiFeO3(0.4)PbTiO3, doped with 3% of La (BFPT-3L) by high energy ball milling at and milled again and micromilling. The study of materials with better physical and mechanical properties for practical applications is becoming increasingly common in high-tech industries, especially nanostructured materials because some properties change at the nanoscale, allowing absolutely unique applications. Searching the decrease of the average grain size of the material until the nanometer order in order to obtain nanostructured ceramic powders with homogeneous stoichiometry. These powders were subjected to successive grindings until reaching the lower limit for the particle sizes around 90 nm and then were sintered by discharge plasma in order to inhibit grain growth during sintering, which showed satisfactory results because it kept the grains sizes of the starting powder, around 90 nm. After this procedure were studied structural, microstructure, electrical and magnetic properties. We verified that the samples are eletrically conductive due to the passage of electrical current which was exposed during sintering and thus it was necessary to perform heat treatment for reoxidation of the sintered material by plasma discharge. Several tests for heat treatment were performed, searching the reoxidation of the samples and in the same time inhibiting grain growth during the process, but it was found that the samples showed up in the metastable state and that with the lowest temperature rise occurs grain growth. Electrical resistivity analyzes were performed as a function of time in which it can be seen that the heat treatment for reoxidation is effective to the reoxidation of the material despite causing a considerable increase in grain, because the reoxidized samples had high electrical resistivity, in GΩ.m order. We have concluded that it is possible to obtain highly dense nanostructured ceramic monoliths by way of physical methods and sintered by discharge plasma, but it has not been possible to reoxidize the samples without a significant growth in grain size.